The burden of low back pain in BRICS: an analysis for the global burden of disease study 2021 - Li Shen; Wencong Cao; Yong Yu; Yong Yu (Frontiers in Public Health)
BackgroundTo analyze the development of low back pain (LBP) disease burden in BRICS countries (Brazil, Russia, India, China and South Africa) from 1990 to 2021 and provide a scientific basis for China and its partner countries to carry out low back pain prevention and transnational medical cooperation.MethodsThe burden of disease for low back pain was assessed by analyzing morbidity, prevalence, years lived with disability (YLD), and other disease burden indicators in BRICS countries in the Global Burden of Disease (GBD) Study from 1990 to 2021. The average annual percentage change (AAPC) was calculated using the Joinpoint regression model. Disease burden and risk factor attribution trends for patients with low back pain in BRICS countries were analyzed from 1990 to 2021. The Bayesian age-period-cohort (BAPC) model was used to predict and analyze future trends in low back pain globally and in BRICS countries.ResultsThe age-standardized incidence rate (ASIR) and age-standardized years lived with disability (ASYLD) for low back pain have generally decreased in China and India, while they have increased in Russia, Brazil, and South Africa. In 2021, the ASIR for low back pain in China was 2,342.46, and the ASYLD was 603.04, with decreases of 26.20 and 26.03%, compared to 1990. In Russia, the ASIR for low back pain in 2021 was 4,529.36, and the ASYLD was 1,206.23, an increase of 16.75 and 15.62% over 1990. In Brazil, the ASIR in 2021 was 3,873.61, and the ASYLD was 1,034.20, representing increases of 19.97 and 21.84%, respectively, compared to 1990. In 2021, the ASIR and ASYLD for low back pain are rising in South Africa, at 2,753.32 and 693.46, with the indices of the increasing trends being 5.46 and 3.04%, respectively, compared to 1990. All the differences observed were statistically significant (p < 0.001). India’s ASIR for 2021 is 2,816.31, down 5.70% from 1990, with no statistically significant trend change (p = 0.634), and the ASYLD is 714.00, a decrease of 8.83% compared to 1990, with no statistically significant trend change (p = 0.322). In BRICS countries, males with low back pain have lower rates of ASIR and ASYLD than females, and the ASIR and ASYLD in BRICS populations increase with age, peaking in the 70+ age group.ConclusionFrom 1990 to 2021, the burden of low back pain declined in China and India, but morbidity and disability-adjusted life years (DALY) remained high. Russia, Brazil, and South Africa are on the rise, and health research on LBP needs to be intensified. Females and the older adult are at high risk of low back pain. Occupational ergonomics and high body mass index (BMI) are major risk factors affecting BRICS countries. The global incidence of LBP from 1990 to 2030 presents a significant downward trend in the future for males and a slight upward trend for females, with an overall global decline.